2015
DOI: 10.5433/1679-0359.2015v36n6p3957
|View full text |Cite
|
Sign up to set email alerts
|

Quality attributes and properties of surubim (Pseudoplatystoma spp.) meat

Abstract: The aim of this study was to evaluate the quality attributes and properties of fillets from surubins (Pseudoplatystoma spp.) reared in cages and fishponds. The design of the study was completely randomized, with two treatments (cage and fishpond) and 16 replicates each. The fillets from fishes reared in cage and fishpond had a mean total weight of 134.71 ± 33.11 g and 151.56 ± 18.56 g, respectively.The following parameters were analyzed: pH, water retention capacity (WRC), color (L* brightness), (a* red), (b* … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
1
2
0
1
Order By: Relevance
“…These values were superior to those reported for fillets of farmed Pseudoplatystoma spp. (48.73 -49.09) (Fantini et al, 2015) and close to those showed for fillets of Pseudoplatystoma sp.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…These values were superior to those reported for fillets of farmed Pseudoplatystoma spp. (48.73 -49.09) (Fantini et al, 2015) and close to those showed for fillets of Pseudoplatystoma sp.…”
Section: Resultssupporting
confidence: 84%
“…Literature reports ranges from 53.94 to 62.53% to fillets of captured Pseudoplatystoma corruscans (Lara et al, 2010), 59.95 to 63.59% of WHC for fillets of farmed Pseudoplatystoma spp. (Fantini et al, 2015(Fantini et al, , 2020, and proximately 68% for fillets of Pseudoplatystoma sp. obtained from the commerce (Honorato et al, 2014).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…A relação entre o rendimento de carcaça e o porte dos peixes é outro aspecto a ser levado em consideração. Na maioria dos trabalhos publicados sobre o assunto, há poucos relatos de diferenças significativas relativas ao efeito do porte dos peixes à despesca e o rendimento de carcaça, e quando há, atribui-se o resultado muito mais à metodologia utilizada para filetagem, à precisão do processo de mecanização, à genética da espécie produzida, ao empenho e treinamento dos funcionários, do que ao tamanho do animal em si (Moraes et al, 2003;Leonhardt et al, 2006;Nguyen et al, 2010;Fantini et al, 2015). Mas por menor que seja, o impacto financeiro destas diferenças deve ser avaliado.…”
Section: Metas Para 2018unclassified